Silver Nanoparticles: Cytotoxic and Apoptotic Activity on HT-29 and A549 Cell Lines - Miri, Abdolhossien; Sarani, Mina (Journal of New Developments in Chemistry, 2018)
Silver nanoparticles (Ag-NPs) are versatile materials with a broad range of applications in various fields such as cancer therapy, drug delivery. In this work, cytotoxic and apoptotic activities of silver nanoparticles was evaluation against lung (A549) and colon (HT-29) cell lines. The cytotoxic activity of nanoparticles was performed by MTT assay, while their apoptotic activity was tested through TUNEL method. The results of MTT of A549 have illustrate that fifty percent of cells destruction in concentrations more than 250 µg/ml of Ag-NPs. Apoptotic results of nanoparticles have shown more than fifty percent of apoptosis on A549 cell line. HT-29 display full apoptosis at concentrations more than 500 µg/ml. It seems that synthesized Ag-NPs by using P. farcta extract can be candidate as anti-cancer agent in treatment many cancers through creating or discovering new drug forms
Keywords: Ag-NPs; Cytotoxic; lung cell line; colon cell line.